Engineering nickel vacancies in NiCo LDH nanoarrays accelerates hydrogen evolution and oxygen evolution reactions. Issue 56 (23rd June 2022) - He, Wenjun; Cao, Da; Ma, Dongqin; Li, Ying; Chen, Cong; Liang, Limin; Liu, Hui
Abstract : NiCo LDH-VNi /CC exhibits excellent HER and OER activities, requiring only 195 and 227 mV overpotentials to achieve a current density of 10 mA cm −2 in 1 M KOH, and sustained for 100 h with almost no degradation. Abstract : Exploring efficient bifunctional electrocatalysts is crucial for constructing water splitting systems. In this work, a bifunctional catalyst, NiCo layered double hydroxide (LDH) nanosheets with nickel vacancies, was fabricated by a hydrothermal and chemical etching method, which requires 195 and 227 mV overpotentials for HER and OER to achieve 10 mA cm −2 and exhibited sustained activity for 100 h with almost no degradation. This study provides a new idea for the rational design of efficient non-precious metal catalysts with defects for water splitting.